A systematic and meta-analytic review of the literature on correctional officers: Identifying new avenues for research. (January 2019) - Butler, H. Daniel; Tasca, Melinda; Zhang, Yan; Carpenter, Channing
Abstract: Scholarly interest in the experiences and behaviors of correctional officers has increased over the past several decades. Yet, considerably less is known about those who oversee and manage prison populations relative to other criminal justice professionals. In this study, we perform a systematic review and meta-analysis of 172 peer-reviewed articles published between 1980 and 2017 that include samples of correctional officers. The goal of this review is to "take stock" of the correctional officer literature in an effort to inform future research, policy, and practice. Specifically, we examine publication trends over the past several decades in addition to examining all outcomes across the included studies. We find that job satisfaction, job stress, and organizational commitment are the most frequently examined outcomes. Next, we examine the most commonly included correlates across each of these outcomes, which include age, female, white, education, experience, supervisor support, and peer support. Findings reveal that organizational factors such as supervisor support and peer support influence each of these outcomes, while demographic characteristics have mixed effects. Recommendations for future research include the need to examine other attitudes and experiences of correctional officers in addition to exploring variation in the effects examined in this review. Highlights: We perform a systematic review and meta-analysis of the correctional officer literature. We examine 172 peer-reviewed publications published between 1980 and 2017. Majority of research on correctional officers is concentrated within three outcomes: job stress, job satisfaction, and organizational commitment. Organizational factors are most frequently associated with job stress, job satisfaction, and organizational commitment.